2022
DOI: 10.48550/arxiv.2201.09026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triple points and novel phase transitions of dyonic AdS black holes with quasitopological electromagnetism

Ming-Da Li,
Hui-Min Wang,
Shao-Wen Wei

Abstract: The quasi-topological electromagnetism has an important influence on the strong gravity of the dyonic black hole. For example three photon spheres with one being stable are found and which is wished to be tested with the observation of EHT. In this paper, we mainly concern the thermodynamics and phase transition for the dyonic AdS black hole when the quasi-topological electromagnetism is included. Quite different from the black hole solution without the quasi-topological electromagnetism, we observe a triple p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…An overview of dyonic fields is dedicated to experiencing the situation of a purely electric source [1] with a part of the magnetic field together in a quasi-topological electromagnetism [51,52]. However, a convenient choice for the gauges fields should be in the following form…”
Section: The Set Upmentioning
confidence: 99%
“…An overview of dyonic fields is dedicated to experiencing the situation of a purely electric source [1] with a part of the magnetic field together in a quasi-topological electromagnetism [51,52]. However, a convenient choice for the gauges fields should be in the following form…”
Section: The Set Upmentioning
confidence: 99%
“…It is now possible to write the thermodynamical quantities related to the black hole [49]. Considering r + as the largest root of f (r + ) = 0 and the negative cosmological constant as positive pressure P = − Λ 8π then the temperature and the entropy are…”
Section: Black Hole Thermodynamicsmentioning
confidence: 99%
“…The aim of this paper is to present the study of the Joule-Thomson in quasi-topological electromagnetism [48], a theory that corresponds to a higher-order extension of Maxwell electromagnetism constructed with the bilinear invariant F 2 = F µν F µν . In [48] the authors also found the corresponding charged AdS black hole and their thermodynamics phase transitions were presented in [49].…”
Section: Introductionmentioning
confidence: 95%
“…An overview of dyonic fields is dedicated to experiencing the situation of a purely electric source [28] with a part of the magnetic field together in a quasi-topological electromagnetism [29,30]. Indeed, We think about the following constraints:…”
Section: The Black Hole Solutionmentioning
confidence: 99%